Current Scenario of Different Type of Services Marketing and Delivery in Customer Relationship Management - Gaikwad Deepak Devendra (International Journal of Engineering and Management Research, 2020)
A Significance of customer relationship management, CRM in banking sector and their benefit to their customer, principles of CRM, challenges for implementation. Profile of sample bank and their working performance were discussed perception of service quality of public and private sectors banks and their expectations in this regard and discussed in forthcoming the social economic profile of the respondents is disused. The concept of CRM is vital to the insurance sector. Good customer service is the bust brand ambassador for any mode of insurance. The entire business process consists of highly integrated efforts to discover, create, arouse and satisfy customer need. The modern business has realized it and is making all out efforts to become customer-centric across the globe. Hence, the customer relationship management is not a once-for-all affair but a continuous process. It is the integral approach of dealing with customer by deploying the advanced information technology. The Hospitality industry a huge potential for Social CRM. The hospitality industry thrives on two basic factors-segmentation & uniqueness. Apart from the regular promises of customer satisfaction, it is the identity or rather the personality on hotel that really matter. Customer relationship management, particularly on hotel chin level, is very challenging but also very important, as the hospitality industry deals with perishable goods and need to mange supply and demand with a sure instinct.